IMPLEMENTATION OF FACILITIES AND INFRASTRUCTURE MANAGEMENT IN PUBLIC ELEMENTARY SCHOOLS - Marmoah, Sri; Adela, Dhea; Fauziah, Muna (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
This study utilized to analyze the implementation of management of school facilities and infrastructure. This type of research is descriptive qualitative conducted in Public Elementary School of 01 Bakipandeyan. Data collection techniques in this study include in-depth interviews (Principals, treasurers, teachers, and school committees) and documentation studies. The validity of the data gathered in this study was technical triangulation (in-depth interviews and documentation) and sources (Principals, teachers, and school committees). Data analysis techniques gather interactive analysis with stages: data reduction, data presentation, and verification. The results showed that the implementation of facilities and infrastructure management in Public Elementary School of 01 Bakipandeyan was carried out through three stages, namely: (1) procurement of facilities (2) utilization and (3) maintenance of facilities and infrastructure. Researchers suggest that schools be better at managing school facilities and infrastructure and looking for specialized workers to manage school facilities and infrastructure.